Merkel cell differentiation in the labial mucous epithelium of the rabbit. - Tachibana, T (1980)
To clarify the relation between the so-called 'transitional' cell and the Merkel cell, the frequency of these cells in the labial mucosal epithelium was compared between infant, juvenile and adult rabbits. The transitional cell was observed in serial ultrathin sections. Transitional cells were most numerous in the infant and juvenile, while the definitive Merkel cell showed a reciprocal increase in number. In the infant and juvenile, the transitional cells differed slightly from each other in their ultrastructure: some resembled immature keratinocytes, others resembled definitive Merkel cells. All transitional cells contained the Merkel cell granules and the intranuclear rodlet. It was interpreted that the Merkel cell in the labial mucous epithelium develops from the transitional cell. Neither definitive Merkel cells not transitional cells were identified in the lamina propria. The present circumstantial evidence favours the hypothesis that Merkel cells differentiate from precursors in the basal layer of the epithelium.